Land surface temperature assessment in relation to land-use/land-cover (A case study: Isfahan City, Central Iran) - Sayyad Asghari Saraskanrood; Bahareh Asadi,; Ehsan Ghale (Caspian Journal of Environmental Sciences)
Most of critical issues such as increase in pollution levels, sudden climatic changes and the rise of temperature in the urban area, leading to the formation of Urban Heat Islands (UHI), have been resulted from urbanization. As population density increases, most terrestrial areas become cities, and cities grow very fast. The reason to do the current study is to compare Single-Channel, SEBAL and Split-Window methods and then choose the best method for estimating land surface temperature. The objectives are as follows: Three independent studies were conducted using a series of Landsat data: (i) to land-use/land-cover (LU/LC) classification by object-oriented method and change detection; (ii) to understand the connection between particular LU/LC class and Land Surface Temperature(LST); and (iii) LST recovery using Single-Channel, SEBAL and Split-Window, as well as comparing these methods together. The results of land-use classification and change detection indicated that urban areas have increased, while agriculture has declined. The results of validation of the three temperature recovery methods demonstrated that due to using two thermal bands simultaneously, the Split-Window method functions better and in these three algorithms, water bodies and wet soils exhibit minimum surface temperatures. Due to less vegetation, areas such as deserts, saline soils and residential area display a higher surface temperature. Vegetation has always been an obstacle for heat input and inversely related to surface heat. In addition, due to fuel pollution of machinery and factory, urban areas experience high temperatures. The only gap of this study was the utilizing 5-cm surface temperature data, which was only available at airports and was not available.